Supporting transplant athletes: perspectives on delivery of a sports performance and well-being service at the British Transplant Games - Duncan, Elaine; Nateri, Rachele; Lind, Abigail; Leddington-Wright, Sheila; Bloxham, Alison; Moffitt, Lindsey; Sykes, David (Frontiers in Sports and Active Living, 2024)
Evidence suggests that engaging in physical activity improves the mental and physical health of transplant recipients. An opportunity to be more active could be participating in the national and international network of Transplant Games. Although the literature on motivations for and the experience of taking part in the Games is available, little is known about what role applied practitioners, specifically sport and exercise psychologists could play as transplant recipients prepare and compete. This paper offers perspectives on the provision of a sports performance well-being service delivered at the British Transplant Games. The paper consists of several sections. The first offers background and how the service came into being. The second provides details of the model and philosophy that underpinned the service delivery. The third includes the trainee and exercise practitioner's casework and the challenges therein. Informed by the team's reflections and post-games survey the final section proposes recommendations for future applied sport and exercise services at this unique event.